Challenges in diagnosis and management of a spiradenocarcinoma: a comprehensive literature review. Issue 10 (1st February 2021) - Wagner, Katy; Jassal, Karishma; Lee, James C.; Ban, Ee‐Jun; Cameron, Rhoda; Serpell, Jonathan
Abstract: Background: Spiradenocarcinoma is a rare skin adnexal neoplasm that may behave aggressively. It is often associated with a benign slow‐growing spiradenoma that has undergone malignant transformation. Given the paucity of cases in the literature, there is a lack of consensus on treatment. Methods: The terms 'malignant spiradenoma' or 'spiradenocarcinoma' were systematically used to search the PubMed, MEDLINE and Google Scholar databases. A total of 182 cases of spiradenocarcinoma were identified as eligible for this comprehensive literature review. Results: Spiradenocarcinoma was commoner in older age and Caucasian race. In most cases, surgical excision for local disease is the mainstay of treatment. Lymph node dissection is usually reserved for those with suspected or confirmed lymph node metastases. High rates of local recurrence (20.8%), metastasis (37.4%) and mortality (19.1%) were identified, prompting some authors to suggest regular follow up including chest X‐rays and liver function tests. Conclusions: Patients with spiradenocarcinoma may benefit from a magnetic resonance imaging and fluorodeoxyglucose‐positron emission tomography/computed tomography to establish the extent of disease. We recommend wide local excision as the treatment of choice to achieve surgical margins of ≥1 cm, with node resection to be determined on a case‐to‐case basis. Regular follow up is important given the high rate of local recurrence, metastasis and mortality. This should include an examination of the regional lymph nodes. Further research is required to refine an evidence‐based approach to spiradenocarcinoma. Abstract : A comprehensive literature review including 182 cases of spiradenocarcinoma was performed. Spiradenocarcinoma was found to be associated with high rates of recurrence (20.8%), metastasis (37.4%) and mortality (19.1%). Surgical excision with wide margins is recommended, reserving lymph node dissection for those with clinically suspicious or biopsy‐confirmed lymph node metastases, although further research is needed to refine an evidence‐based approach.